2020
DOI: 10.1007/s10681-020-02663-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospects to select tall fescue with a low silica concentration

Abstract: Although not essential to most plant species, silica plays an important role in the protection of plants against different types of stress. In monocots, the main role of silica is protection against herbivores. Although the mechanisms are not fully understood yet, it is clear that silica discourages the grazing of herbivores. Hence, high silica concentrations are unwanted in forage crops and grasses that are grown as a feed for ruminants. In this paper, we explored the possibilities to select forage grasses wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It may consequently also have high silica content. In contrast, amongst the grasses studied, Cougnon et al ( 2020 ) found perennial ryegrass to contain the lowest concentrations of silica. Although at this stage speculative, possible respiration rate and silica content differences between the grasses could influence DM losses during wilting of Festulolium spp.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It may consequently also have high silica content. In contrast, amongst the grasses studied, Cougnon et al ( 2020 ) found perennial ryegrass to contain the lowest concentrations of silica. Although at this stage speculative, possible respiration rate and silica content differences between the grasses could influence DM losses during wilting of Festulolium spp.…”
Section: Resultsmentioning
confidence: 86%
“…Although previously considered a negative trait for intake of grass forage by grazing animals, silica content is now receiving new attention as a means of diversifying grasslands to combat the impact of climate change (Volaire et al, 2014). In a study by Cougnon et al (2020) comparing silica concentrations in different forage grass species, the highest silica concentrations were found in fescue, albeit in tall fescue (Festuca arundinacea Schreb.). Although its silica content has not yet been reported, F. arundinacea var glaucescens is a progenitor of tall fescue and has contributed two of its three ancestral genomes (Humphreys et al, 1995).…”
Section: Other Factors Affecting Proteolysis During Ensilagementioning
confidence: 99%
“…Its significant advantage is forming rhizomes, which are more resistant to tearing, facilitating easier recovery (if tears happen) compared to the bunch-type perennial ryegrass or tall fescue [2]. Tall fescue creates a deep root system, making this species the most tolerant to drought among the three investigated species [3,4].…”
Section: Introductionmentioning
confidence: 99%